2019
DOI: 10.1111/ajad.12898
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use Disorder and Epilepsy: A Cross‐National Analysis of 657 072 Hospitalized Patients

Abstract: Background and Objectives Recent evidence has suggested that cannabis use precipitates cerebrovascular events. We investigated the relationship between cannabis use disorder (CUD) and hospitalization for epilepsy. Methods Nationwide inpatient sample (NIS) was analyzed from 2010 to 2014 for patients (age 15‐54) with a primary diagnosis of epilepsy (N = 657 072) and comparison was made between patients with ICD‐9 classification of CUD and without CUD. We utilized logistic regression to study the association (odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Mood and anxiety disorders, suicidal behaviors, and psychotic disorders were significantly associated with pediatric POD inpatients having CUD [22]. Youth with CUD at an earlier age have a greater risk of long-lasting cognitive impairment and several psychiatric and medical conditions [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Mood and anxiety disorders, suicidal behaviors, and psychotic disorders were significantly associated with pediatric POD inpatients having CUD [22]. Youth with CUD at an earlier age have a greater risk of long-lasting cognitive impairment and several psychiatric and medical conditions [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…TBI increases the risk of addiction by reducing the cognitive ability to perceive negative consequences and increases the perception of gains perceived by drinking and substance abuse [23]. A study by Patel et al found that cannabis abuse among youth increases the risk of intracranial injury by 1.3 times [24]. Binge alcohol drinking is also a risk factor for TBI due to falls and assaults and MVA.…”
Section: Discussionmentioning
confidence: 99%
“…We included patients (age 15-54) with a primary ICD-9 discharge diagnosis for arrhythmia as shown in Table 20 Patients coded as "in remission" from cannabis abuse or dependence were excluded from our sample to maintain the homogeneity of the study cohort. Patients below 15 years and above 54 years of age were excluded from the sample to limit our analysis to the middle 90th percentile of the cannabis users.…”
Section: Inclusion and Exclusion Criteria And Outcome Variablesmentioning
confidence: 99%
“…Patients below 15 years and above 54 years of age were excluded from the sample to limit our analysis to the middle 90th percentile of the cannabis users. 20 Demographic variables studied included age group (15-24, 25-34, 35-44, 45-54), gender (male or female), and race (Caucasian, African American, Hispanic, or other). 19 The existing risk factors for cardiac arrhythmia were based on the past literature and identified using ICD-9…”
Section: Inclusion and Exclusion Criteria And Outcome Variablesmentioning
confidence: 99%